Education, Semiotics and the Spirit of the Time: a methodology for educating university technological professional in post-pandemic Brazil (Revista de Ensino em Artes, Moda e Design, 2021)
We live in an accelerated future, as the futurologists have been saying. In fact, the temporalityinstituted by the pandemic anticipates many changes that were already underway, such as theinstitutionalization of homework, online education, the even greater relevance of sustainabilityin its broadest sense and the social demand for companies and brands to be more sociallyresponsible. Other changes, that have been embryonic up to now, become more evident, suchas the strengthening of values of solidarity and empathy, the transformation of individualpractices into collective actions – staying at home and using mask are also used as a practice of collective respect, concern to others –, in addition to questioning the economic modelsthemselves, such as the proposal of shifting shareholder capitalism, focusing exclusively onfinancial and short-term, into another dynamic that takes into account all stakeholders,accelerating the criticisms of the society model based on hyperconsumption.Within these profound transformations, new professions, new ways of life, new ways ofteaching and learning are being established. Valuing experiences, reinforcing ways of life thatcontribute to a more just and solidary society, will become even more relevant in a pandemicand post-pandemic world. At a time when empathy is so valued, reestablishing the most basicforms of relationship between people becomes indeclinable, highlighting collective attitudesthat dignify the subject, understanding his life story. Renegotiating new collective and groupactions becomes primordial, which includes new ways of learning, teaching and coexisting.That is what education needs right now. A perspective of respect for the subject's path, for lifenarratives, not only transporting the teaching-learning process into digital platforms, which isnot exactly new.In this moment of subverted daily lives, of digitized spaces, of “visible” inequalities, ofdisconnected connectivity, it is necessary to develop a process of trust that gives meaning tothe “new” relationships between teacher, student, teaching (as a substance to be apprehendedand learned) and technologies. Trying to adjust to the time, making sense of the senselessmoment. Losing the fear of interacting, trusting the other as a partner in the process ofreciprocal construction of knowledge when faced with remote, virtual classes, in “supervisibility”discussion spaces, initiatives that may even be experienced as a normal life practice,for some, but certainly arousing much concern for others.The objective of this article is to briefly understand and analyze the challenges faced byeducation in Brazil in this current pandemic moment and, at the same time, to proposemethodological paths that can address such challenges regarding to the technological issuesthat education, in digital environments, creates and establishes both for teachers and students– and, eventually, for their families –, in the face of regarding social, cultural and educationalinequalities, which this present time has been intensifying, as well as facing an inevitable newscenario for technological university education, which will need to be rewritten in the postpandemiccontext.As it is observed today, and as it will possibly be observed in the near future, not everyone cantravel to higher education centers and, in this way, it is also proposed, in this work, to thinkabout a methodology based on use of Digital Information and Communication Technologies(DICT) in university technological education, which is commonly excluded from more consistent discussions in relation to the teaching-learning process, although considering theincorporation of technologies within a more humanistic, sensitive and welcoming view.Sometimes, the geographical hierarchy ends up centralizing what should be decentralized,such as democratizing access to quality education for all. In this aspect, and in confronting thesocial injustices demarcated, also by the territoriality, it is that a “look broadly”, a “learncollectively”, can impact in more solidary and respectful attitudes, with broad, unrestricted andinclusive participation.This new form of interaction, teacher-student-technology, moves towards a minimallyconsistent methodological proposal to face the challenges of the current moment of universitytechnological education. Thus, the dialogue was established between the Pedagogy ofAutonomy, by the educator Paulo Freire, defender of a pedagogy founded on ethics, respect,dignity and autonomy of the student, and the interaction regimes - and even of regimes ofsense - from Eric Landowski's sociosemiotics, trying to understand the new teaching practicesthat are being established sometimes in the mediated presence of teacher and student,sometimes in their virtualized presences, in an asynchronous way, in a path that, at thismoment, is set as necessary.Therefore, it will be sought, in a brief way, to associate the elementary forms of educationalpractices, from the perspective of socio-semiotics, from Landowski's interactional regimes, toFreire's criticality of curiosity. In other words, a knowledge produced in action, a "blooming" inthe interaction, which puts in relationship the naive curiosity with criticism to a knowledge, toan "awakening", to a passion to know, transforming this knowledge, as Freire says, into anepistemological curiosity, in a related knowledge that motivates a broader understanding ofreality. Know the own space, reflect on it and provoke changes through out a systematizedknowledge, with constant debates, valuing the individual and his path, in line with the teachingcontents.In these new mediated and virtualized interactions, in which different types of distances areobserved between people, inclusion, in the broad sense of the term, becomes fundamentaland should generate a space for social well-being, motivating practices that foster more humaneducational actions in the face of all digital transformation, with an irresistibility to the valuesof cooperation, tolerance and mutual respect; welcoming actions, therefore.Thus, it is necessary to promote social inclusion actions for the transformation and respect forthe community at this unique moment. The OFÉ Institute was created in this direction, objectingto offer high quality education, to be a reference in university technological professional education, based on innovation, social justice, sustainable, participatory and ethicalmanagement, in order to promote local and regional development by means of a humane,sensitive, welcoming methodology, with certification in stages, and which values the subject'spath based on a hybrid teaching with welcoming. The term OFÉ, chosen to name the Institute,a word in Yorubá to designate a form of magic that makes a person light, to the point of floatingin the wind and jumping very high, is a way of honoring our African ancestry and language anda way of representing all segments that did not have the same social and educationalopportunities in the development of Brazilian society, with a commitment to take universitytechnological professional education, with quality, to less privileged segments of society, inorder to contribute to the reduction of educational and social dissymmetry.The word OPÔ, chosen to name the methodology, is a term in Yorubá, which designatesfullness, plurality for all, a way of highlighting the possibility of offering university technologicaleducation for all. As a proposal to combat inequalities, due to the lack of opportunities, it willalso be worked in the perspective of family welcoming, providing the dependents of studentswith the possibility of entering professional courses, associated with craftsmanship andgastronomy practices, available through the ÒNÀ core, which in Yorubá means path, road,access. Linked to OFÉ Institute, this center aims to develop competencies and skills to providefuture generation of income and employability to the family nucleus, with a proposal to alwaysact collectively and in solidarity.
Keywords: Education; Semiotics; Methodology